Myoclonus in Angelman Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A clinical and electroencephalographic study of 11 unrelated patients with Angelman syndrome (AS), confirmed by genetic analysis, is reported from the University of Pisa, Italy.